2022
DOI: 10.1182/blood.2021014506
|View full text |Cite
|
Sign up to set email alerts
|

Timing of high-dose methotrexate CNS prophylaxis in DLBCL: a multicenter international analysis of 1384 patients

Abstract: Prophylactic high-dose methotrexate (HD-MTX) is often used for diffuse large B-cell lymphoma (DLBCL) patients at high risk of central nervous system (CNS) relapse, despite limited evidence demonstrating efficacy or the optimal delivery method. We conducted a retrospective, international analysis of 1,384 patients receiving HD-MTX CNS prophylaxis either intercalated (i-HD-MTX) (n=749) or at the end (n=635) of R-CHOP/R-CHOP-like therapy (EOT). There were 78 CNS relapses (3-year rate 5.7%), with no difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 34 publications
3
47
0
Order By: Relevance
“…High-dose methotrexate at various doses during or following chemoimmunotherapy was not associated with a significant reduction in CNS relapse (8•4% with high-dose methotrexate vs 9•1% without high-dose methotrexate, p=0•1). 50 Furthermore, in a retro spective cohort of 1384 patients who all received high-dose methotrexate, 3-year CNS relapse risk was 9•1% in 600 patients with DLBCL and CNS-IPI scores were 4-6, 23 remarkably similar to the cohorts examined in the original CNS-IPI development and validation cohorts (10•2%) where minimal CNS prophylaxis was used.…”
Section: Agents Used and Evidence Basementioning
confidence: 64%
See 3 more Smart Citations
“…High-dose methotrexate at various doses during or following chemoimmunotherapy was not associated with a significant reduction in CNS relapse (8•4% with high-dose methotrexate vs 9•1% without high-dose methotrexate, p=0•1). 50 Furthermore, in a retro spective cohort of 1384 patients who all received high-dose methotrexate, 3-year CNS relapse risk was 9•1% in 600 patients with DLBCL and CNS-IPI scores were 4-6, 23 remarkably similar to the cohorts examined in the original CNS-IPI development and validation cohorts (10•2%) where minimal CNS prophylaxis was used.…”
Section: Agents Used and Evidence Basementioning
confidence: 64%
“…A recent large retrospective study addressed the question of high-dose methotrexate timing, comparing patients receiving high-dose methotrexate delivered either intercalated (n=749) or at end of R-CHOP (n=635). 23 Delays to R-CHOP of 7 days or more were significantly increased with intercalated high-dose methotrexate versus delivery at the end of R-CHOP, with 20% of intercalated high-dose methotrexate treatments associated with a delay to subsequent R-CHOP. There was no difference in CNS relapse rate between the groups, including on multivariable analyses and when restricting analyses to the highest-risk patients.…”
Section: Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…cytarabine, ifosfamide, etoposide) crossing the blood-brain barrier (BBB) seemed more promising (7,9). However, randomized studies comparing prophylactic strategies have not been reported and more recent analyses shed doubts if IV HD MTX is more effective than IT MTX or has any preventive effect at all (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%